The effectiveness of differentiation strategies on company performance: a case of Gtel Zimbabwe - Muzadzi, Sheila (Midlands State University, 2018)
The research aimed at determining the effectiveness of differentiation strategies on company performance investigating. Due to the intense competition faced by Gtel and the flooded mobile market, the researcher saw it fit to propose the implementation of differentiation as a strategy that will help the company to upgrade and revive company performance. The research objectives were to find out if product differentiation affects competitive advantage, to determine if personnel differentiation affects customer satisfaction and to find out if customer service differentiation influences repeat purchases. The concept of differentiation was discussed to give an overall introductory insight to the research. Various opinions of authors have been reviewed with an objective of getting a clear understanding of the research objectives. Exploratory and descriptive research designs were used to search for information relating to differentiation strategies. Primary and secondary data sources were used for the research. Questionnaires and interviews were used to collect primary data. The company sales reports, yearly journals and customer database were used as a secondary data source. A target population of 460 was used and then a sample size of 92 was drawn constituting of customers and employees. Convenience and judgemental sampling techniques were used in this research. The collected data was presented using different pictorial illustrations such as tables, pie charts and graphs. Analysis of data was done using the results collected and discussion of the findings were made putting other authors’ views into consideration. The researcher drew conclusions from the findings for each objectives and the differentiation concept as a whole and different views of authors were used. The researcher went on to give recommendations to the company on the basis of the information gathered and reviewed literature as well as recommending areas of further study.